The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/bjc.2014.564
|View full text |Cite
|
Sign up to set email alerts
|

QTc interval prolongation with vascular endothelial growth factor receptor tyrosine kinase inhibitors

Abstract: Background:Multi-targeted vascular endothelial growth factor receptor (VEGFR) tyrosine kinase inhibitors (TKIs) are known to cause cardiac toxicity, but the relative risk (RR) of QTc interval prolongation and serious arrhythmias associated with them are not reported.Methods:We conducted a trial-level meta-analysis of randomised phase II and III trials comparing arms with and without a US Food and Drug Administration-approved VEGFR TKI (sunitinib, sorafenib, pazopanib, axitinib, vandetanib, cabozantinib, ponati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 46 publications
3
83
0
4
Order By: Relevance
“…4.4% of patients treated with TKIs developed all grade QTc prolongation and 0.8% developed serious arrhythmia (99). However, the incidence of QT prolongation is not affected by the duration of therapy (99).…”
Section: Qt Prolongationmentioning
confidence: 99%
See 1 more Smart Citation
“…4.4% of patients treated with TKIs developed all grade QTc prolongation and 0.8% developed serious arrhythmia (99). However, the incidence of QT prolongation is not affected by the duration of therapy (99).…”
Section: Qt Prolongationmentioning
confidence: 99%
“…However, the incidence of QT prolongation is not affected by the duration of therapy (99). The most common drugs that prolongs QTc when used in conjunction with sunitinib are domperidone or loperamide (104); nonetheless, there were no high-grade arrhythmias or sudden cardiac deaths associated with sunitinib use.…”
Section: Qt Prolongationmentioning
confidence: 99%
“…It is noteworthy that hypertension caused by tyrosine kinases inhibitors is associated with several fatal complications, such as left ventricular ejection fraction (LVEF) dysfunction, cardiac failure and coronary artery disease [37][38][39]. Previous reports analysed the incidence of cardiac events in patients treated with sorafenib and consequently revealed that 33.8% experienced a cardiac event with typical symptoms or with changes in ECG and biochemical indicators (CK-MB, TNT) [37].…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…Additionally, a randomized, doubleblind, placebo-controlled trial of repeated oral doses of pazopanib in patients with solid tumors revealed a concentration-dependent decrease in heart rate and a small concentration-independent prolongation of the QTcF interval [14]. A recent trial-level meta-analysis of 6548 patients treated within randomized phase II and III trials comparing arms with and without a FDA-approved VEGFR TKI reported that these can be associated with QTc prolongation albeit of low clinical significance [15]. Notably, regorafenib was not included in this analysis because QTc prolongation was not listed as an adverse event in any of the trials.…”
Section: Discussionmentioning
confidence: 99%